Augmented Reality for Geometry Learning in Primary Education: A Systematic Literature Review - Irmaniyah Irmaniyah; Dewi I. S. Nasution; Eliyah Barizah; Syarifah Syarifah (Journal of Social Work and Science Education, 2026)
This systematic literature review examines the effectiveness of Augmented Reality (AR) technology in improving geometry learning outcomes at the primary education level in Indonesia. Following the PRISMA 2020 guidelines, a comprehensive search was conducted across Google Scholar, Sinta, and Garuda databases for articles published between 2020 and 2025. Of 100 initially identified articles, 35 met the inclusion criteria and were subjected to descriptive qualitative analysis and meta-synthesis. The findings reveal that AR-based learning media significantly improve students’ geometry learning outcomes, with N-Gain scores ranging from 0.40 to 0.87 (moderate to high categories). AR enhances learning by visualizing abstract geometric concepts as interactive 3D models, increasing student motivation (from 39.67% to 92.67%), and facilitating spatial understanding. Key challenges include infrastructure limitations, teacher readiness, technological accessibility, and curriculum integration. The review identifies the ADDIE model as the most prevalent development framework and highlights the potential of integrating ethnomathematics with AR for culturally relevant learning. This study provides theoretical and practical foundations for AR integration in geometry teaching and recommends systematic teacher training, infrastructure improvement, and adaptive learning models for future implementation. Future research should employ longitudinal designs and expand participant contexts to strengthen empirical evidence.